Prototipe alat bantu ukur dimensi kendaraan bermotor berbasis mikrokontroler - A. Novianto; B. Istiyanto; A. Siswono (Dinamika Teknik Mesin, 2024)
This research is a type of research and development (R&D) research whose output produces a design product for tools to measure the dimensions of motorised vehicles. The goal is to create a vehicle dimension measurement device that is portable, quick, accurate, and easy to use. The design of the tool consists of various components that are interconnected into a series, which is then programmed according to needs. The way the series of tools work is by emitting infrared light through a laser distance sensor, which will then be reflected on the reflector in the support tool. The data will be processed using an ESP32 microcontroller, and the measurement results can be seen via the LCD module and printed out via a thermal printer. This microcontroller-based prototype of a motor vehicle dimension measurement tool can measure vehicle dimensions more quickly and accurately compared to manual measurements. The use of a support tool is more effective in determining the outermost part of the vehicle compared to the manual method using poles and roll metres, which involves more than three people. The Microcontroller-Based Digital Motor Vehicle Dimension Measuring Tool Prototype works according to the Arduino programming that has been previously designed. The results of the comparison test between the measurement results from the prototype tool and the data from BPLJSKB show a significance value (P) of 0.125. With a significance value greater than 0.05, it can be concluded that the measurement results from this tool are not significantly different.